Effect of Temperature and Strain Rate on the Brittleness of China Sandstone - Xiuyuan Yang; Zhenlong Ge; Qiang Sun; Weiqiang Zhang (Geofluids)
To quantitatively study the influence of temperature and strain rate on the brittleness of sandstone, the mechanical parameters of sandstone under different temperatures and strain rates are collected from the previous literature, and two empirical equations for calculating rock brittleness are used to quantitatively calculate and evaluate the brittleness of sandstone. The results show that both BI1 and BI2 can characterize the brittleness of sandstone, but the applicable conditions are different. The BI1 method is more accurate in calculating the variation in the sandstone brittleness with a strain rate, while the BI2 method is more accurate in calculating its variation with temperature. The brittleness of sandstone increases with the increase in the strain rate, especially when the strain rate exceeds 100 s-1. Under low-temperature conditions, the strength and brittleness of rocks increase due to the strengthening of ice. Under the condition of high temperature, the thermal damage to sandstone is intensified after 400°C, and the quartz phase changes after 600°C, which leads to the increase in microcrack density and the decrease in brittleness of sandstone. The conditions of low temperature and high strain rate are beneficial to the enhancement of sandstone brittleness.